2013
DOI: 10.1016/j.cps.2013.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Tumescent Liposuction

Abstract: The evolution of liposuction has been multidisciplinary. The tumescent variant was developed using dilute local lidocaine and epinephrine and was meant to specifically exclude additional intravenous sedation, regional or general anesthesia, and intravenous fluids. Clinical pharmacology, pathophysiology, and safety studies are reviewed in this article. Tumescent formulations for varied anatomic sites are discussed, as well as other indications for tumescent anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…To obtain the patients fat for grafting, liposuction is used and can be tumescent. Tumescent liposuction is a variant of liposuction and involves infiltration of a warmed saline solution dilute with epinephrine, with or without lidocaine, within the targeted fat aspirate region using a liposuction cannula . The fat aspirate obtained from liposuction is harvested and centrifuged in a closed, clean circuit for minimal mechanical damage and maximum viability of adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain the patients fat for grafting, liposuction is used and can be tumescent. Tumescent liposuction is a variant of liposuction and involves infiltration of a warmed saline solution dilute with epinephrine, with or without lidocaine, within the targeted fat aspirate region using a liposuction cannula . The fat aspirate obtained from liposuction is harvested and centrifuged in a closed, clean circuit for minimal mechanical damage and maximum viability of adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Because patients often undergo general anesthesia, lidocaine subcutaneous anesthesia seems unnecessary because lidocaine could compromise SVF and ASC survival in the lipoaspirate. 18,26,27 For example, in our previous study, 18 we have reported that lidocaine has significant and a negative impact on ASC survival in the lipoaspirate that is used for fat grafting.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 It can be achieved through a method of infusing large volumes of solution, which contain diluted anesthetic with epinephrine. Lidocaine is the most widely used anesthetic in tumescent anesthesia.…”
mentioning
confidence: 99%
“…Although not technically minimally invasive, tumescent liposuction is another well‐established procedure for the primary management of localized adiposity in nonobese patients. This surgical “sculpting” in the nonobese population remains the gold standard for subcutaneous lipoplasty, given the ability of microcannulas to rapidly avulse smaller volume fatty deposits from precise areas with nominal risk to underlying structures or overlying skin . Liposuction in the nonobese population is associated with rapid recovery, excellent cosmetic results, and minimal postoperative morbidity .…”
Section: Therapeutic Options For Nonobese Patients With Central Abdommentioning
confidence: 99%